ANALYSIS OF PHYSICAL FITNESS GYMNASTICS JABAR JUARA THROUGH THE STUDY OF LUNG VITAL CAPACITY IN ELEMENTARY SCHOOL CHILDREN IN CIAMIS WEST JAVA - Nugraha, Hilman
Background: The most important indicator of health support is in terms of the cardiovascular or respiratory system, which can be seen from the value of the vital capacity of students' lungs. There are several steps to improve student health with exercise, one of which is often given by teachers, namely physical fitness exercises. Aspects obtained in fitness exercises can train a student in terms of motor, mental, emotional and moral and social. As a result of the reduced physical activity of students in various areas including SDN 4 Sukamantri with an altitude of 842 meters above sea level and SDN 1 Beber Cimaragas with an altitude of 135 meters above sea level, physical fitness exercises can be used as a tool to improve students' health and fitness indicators. Based on direct observation of how the effectiveness of physical fitness exercises jabar juara on lung vital capacity in elementary school students in Ciamis, West Java. Methods: This research is an experimental study used to determine the effect of independent variables with treatment on the dependent variable under controlled conditions, the research design used is "Pretest - Posttest Control Group Design, the research subjects are elementary school students aged 11 and 12 years at SDN 4 Sukamantri with an altitude of 842 meters above sea level and SDN 1 Beber Cimaragas with an altitude of 135 meters above sea level located in Ciamis Regency, West Java. Results: Based on the results of the comparison test calculation, it can be seen that the vital lung capacity of students of SDN 4 Sukamantri with an altitude of 842 meters above sea level and SDN 1 Beber Cimaragas with an altitude of 135 meters above sea level who received the intervention experienced a significant increase compared to students who did not receive the intervention. Two average values in two groups are said to be significantly different if they have a probability value smaller than 0.05 and vice versa. However, students who are in SDN 4 Sukamantri with an altitude of 842 meters above sea level have a higher probability value of lung vital capacity, which is 0.048 and 0.005. Conclusion: Physical fitness gymnastics jabar juara can affect lung vital capacity in elementary school students at SDN 4 Sukamantri and SDN 1 Beber Cimaragas in Ciamis Regency, West Java.